Pastelle - Kinniburgh, Helen; Leech, Judy (Macmillan Education Australia South Melbourne, Vic., 1997)
Pastelle by Helen Kinniburgh is a whimsical children's book that follows the story of a young girl named Pastelle, who has a unique gift for creating colorful, magical art that brings joy to those around her. As she navigates her world, Pastelle learns to embrace her creativity and the importance of self-expression. When her vibrant creations start to fade, she embarks on a journey to discover the true source of her magic and how to keep her colors alive. Through her adventures, she encounters various characters who inspire her and teach her valuable lessons about friendship, perseverance, and the power of imagination. The story is beautifully illustrated, capturing the essence of creativity and the joy of art.